A novel hybrid technique to enhance oil production from oil-wet carbonate reservoirs by combining a magnetic field with alumina and iron oxide nanoparticles. (25th January 2021) - Amrouche, Farida; Gomari, Sina Rezaei; Islam, Meez; Xu, Donglai
Abstract: This paper examined a new study into the effect of combined magnetic field and nanoparticles (NPs) on oil-wet carbonate reservoirs. A novel hybrid enhanced oil recovery (EOR) technique was used to investigate the effect of a magnetic field and aluminium oxide (Al2 O3 ) and iron oxide (Fe2 O3 ) nanoparticles (NPs) on oil recovery from Austin chalk, based on measurements of contact angle, surface tension, rock compaction and rock surface charge. An Amott cell with a surrounding magnetic belt was used to perform spontaneous imbibition tests. When oil-wet cores with an extremely low recovery factor (RF) of 2.73% were imbibed with deionized water, the effect of the combination of magnets and alumina was pronounced and an incremental RF of 14.7% was recorded. However, changing the displacing fluid from deionized water to seawater led to a lower recovery of 9.2%, which can be attributed to the poor dispersion of alumina NPs. Adding iron oxide NPs to the displacing fluid in the presence of magnets also resulted in higher recovery factors, with increases of 22.27% and 12.78% observed for deionized water and seawater respectively. The analysis of zeta potential, contact angle and surface tension data suggests that the combined driving mechanisms of alteration in wettability and interfacial forces caused the improvements found in oil recovery from oil-wet carbonate rocks during water-based nanoparticle flooding when exposed to a magnetic field. In addition, concentrations of aluminium oxide and iron oxide NPs were reduced by factors of 40 and 5 respectively compared to previous studies. Hence, this technique offers cleaner EOR, allows the oil industry to optimize oil production with the lowest chemical use by implementing magnets, ultimately increasing revenue in the long term. Graphical abstract: Image 1 Highlights: A novel hybrid EOR technique was investigated. Iron oxide NPs performed more effectively than Alumina NPs. Hybrid EOR technique increased oil recovery from 2.5% to 25% and 18% respectively. Iron oxide NPs behaved as surface-active components in oil/brine/carbonate systems. Wettability alteration, PDI and oil droplet coagulation are the dominant mechanisms.